2004
DOI: 10.1113/jphysiol.2004.073742
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin advances the circadian timing of EEG sleep and directly facilitates sleep without altering its duration in extended sleep opportunities in humans

Abstract: The rhythm of plasma melatonin originating from the pineal gland and driven by the circadian pacemaker located in the suprachiasmatic nucleus is closely associated with the circadian (approximately 24 h) variation in sleep propensity and sleep spindle activity in humans. We investigated the contribution of melatonin to variation in sleep propensity, structure, duration and EEG activity in a protocol in which sleep was scheduled to begin during the biological day, i.e. when endogenous melatonin concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 62 publications
3
85
0
3
Order By: Relevance
“…It has been previously shown that the amplitude of nocturnal melatonin secretion is significantly greater after daytime exposure to bright light than with exposure to dim light (39). Such a mechanism could very well explain the current sleep quality data because melatonin is known to have sleep-promoting properties (40,41). In addition, it has been shown that increased illumination is able to improve rest-activity rhythms in several populations, such as the elderly (42) and those with dementia (43).…”
Section: Discussionmentioning
confidence: 77%
“…It has been previously shown that the amplitude of nocturnal melatonin secretion is significantly greater after daytime exposure to bright light than with exposure to dim light (39). Such a mechanism could very well explain the current sleep quality data because melatonin is known to have sleep-promoting properties (40,41). In addition, it has been shown that increased illumination is able to improve rest-activity rhythms in several populations, such as the elderly (42) and those with dementia (43).…”
Section: Discussionmentioning
confidence: 77%
“…This is in accordance with the observations by others that exogenous melatonin administration either minimally or does not at all affect PSG sleep measures in healthy individuals (Cajochen et al, 1997;Wyatt et al, 2006) or insomnia sufferers (Luthringer et al, 2009) when administered during the phase of endogenous melatonin secretion. It appears from studies in healthy individuals that exogenous melatonin administration only affects sleep when endogenous melatonin levels are low (Rajaratnam et al, 2004;Stone et al, 2000;Wyatt et al, 2006). Temazepam and zolpidem improved sleep by increasing TST, NREM sleep duration and sleep efficiency, amongst other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep scheduled outside the phase of nocturnal melatonin secretion is disrupted and characterised by delayed sleep initiation and reduced sleep consolidation, and this can be alleviated by exogenous melatonin administration, and several studies have demonstrated this in healthy individuals (Rajaratnam et al, 2004;Stone et al, 2000;Wyatt et al, 2006). The effects of melatonin are thought to be mediated primarily by MT1 and MT2 receptors, which have a high density in the suprachiasmatic nucleus of the hypothalamus, amongst other areas (Arendt and Rajaratnam, 2008;Srinivasan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings come from an extended sleep protocol. Chronic administration of melatonin in a slow-release formulation during a 16-h sleep opportunity begin ning at 16:00 h resulted in a redistribution of sleep so that sleep efficiency during the first half of the sleep opportunity was substantially higher during melatonin treat ment compared to placebo (Rajaratnam et al, 2004). These two studies provide strong support for the hypothesis that exogenous melatonin attenuates the wakepromoting signal of the endogenous circadian pacemaker, allowing for increased sleep efficiency at circadian phases corresponding to the habitual wake episode.…”
Section: B Effects Of Exogenous Melatonin On Human Sleep and Wakefulmentioning
confidence: 99%